A tool to measure socio-economic status of dairy farmers - KADIAN, K S (The Indian Journal of Animal Sciences, 2014)
The socio-economic status (SES) of the farmers referred to the position of an individual or his family member held in the society. The socio-economic status scales developed earlier are not exactly suitable in the present changed socio- economic scenario and rural situation. The need for appropriate socio-economic status measuring tool has been felt with relevant indicators to suit the present scenario. The selected indicators of the socio-economic status scale were referred to 80 judges to get the mean relevancy score. The correlation co-efficient of the scale was observed to be 0.82. It proves a quite high temporal reliability and stability of scale.